The incision angle of mediolateral episiotomy before delivery and after repair - Kalis, Vladimir; Karbanova, Jaroslava; Horak, Miroslav; Lobovsky, Libor; Kralickova, Milena; Rokyta, Zdenek (International journal of gynaecology and obstetrics: the official organ of the International Federation of Gynaecology and Obstetrics, 2008)
OBJECTIVE: To assess the relevance of the suture angle when evaluating mediolateral episiotomy, and the safety of the accepted lower limit of 40 degrees for the incision angle. METHOD: The angles formed by the incision and suture lines with the midline were measured, and any perineal tear noted, in 50 consecutive women undergoing their first vaginal delivery. RESULTS: The angles were significantly different (40 degrees and 22.5 degrees , respectively; P<0.001). The only variable significantly linked to the difference was the timing of the episiotomy. CONCLUSION: The suture angle cannot currently be used to assess the adequacy of the incision angle; moreover, an incision angle of 40 degrees is probably too acute to prevent potential sphincter damage.
Keywords: perineum; kohortové studie; anální kanál; Postoperative Complications; epiziotomie; Suture Techniques; Cohort Studies; šicí techniky; Pregnancy; těhotenství; Perineum; Adult; dospělí; pooperační komplikace; Episiotomy; Anal Canal; Time Factors; lidé; ženské pohlaví; Humans; časové faktory; Female